Know and follow rules - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit, 2005)
Teaches children the importance of knowing and obeying the rules in school and other places. Includes activities.
Book Links (A.L.A.)
1.5
K-3.
K-3
Keywords: Obedience -- Juvenile literature; School children -- Conduct of life -- Juvenile literature; Behavior; Obedience; Human behavior; Obedience; Rules